Situating, anatomizing and enunciating Singapore literature prize - Understanding Singapore's new cultural field. - Wong, Winifred Li Min. (2011)
This research project aims to use the analysis of Singapore Literature Prize (SLP) to understand Singapore’s new cultural field. The cultural prize is chosen to be the focal lens because, as this paper will show, it is the quintessential embodiment of the new arrangements and relationships that characterize Singapore’s contemporary cultural field. By situating SLP’s formation in Singapore cultural policies, we can understand why the cultural field changed. By anatomizing SLP into its many players ― the administrators, sponsors, judges, artists, community and academics ― and dissecting each of their capital intraconversions, we can understand how the new cultural field works. By enunciating SLP’s role in Singapore’s new cultural field, using the case study of its four English fiction winners, we can understand what stance a ‘genuine’ cultural mechanism/ practitioner can take in this new field. It is the hope of this research project to illuminate Singapore’s new cultural field so that cultural practitioners and audience (which effectively include everyone) can understand their cultural production and consumption.